Complete the following statements using m(x) = x² and n(x) = x – 3. m(n(x)) = m(x – 3) = ( X, -3, 0r X-3 )² n(m(x)) = n(x²) = x²

Question

Complete the following statements using m(x) = x² and n(x) = x – 3.
m(n(x)) = m(x – 3) = ( X, -3, 0r X-3 )²
n(m(x)) = n(x²) = x² – (-3,3, or 9)
Because m(n(x)) is NOT EQUAL TO, EQUAL TO, or IS LESS THAN n(m(x)), the composition of m and n is not commutative. Therefore, function composition is not commutative.

in progress 0
Linh Đan 1 year 2021-09-03T17:45:17+00:00 2 Answers 17 views 0

Answers ( )

    0
    2021-09-03T17:47:05+00:00

    Answer:

    x-3 or third option

    3 or second option

    is not equal to or first option

    Step-by-step explanation:

    0
    2021-09-03T17:47:11+00:00

    Answer: x-3, 3, is not equal to

    Step-by-step explanation:

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )